Open innovation environments as knowledge sharing enablers: the case of strategic technology and innovative management consortium. Issue 5 (26th October 2020) - Crupi, Antonio; Del Sarto, Nicola; Di Minin, Alberto; Phaal, Rob; Piccaluga, Andrea
Abstract : Purpose: This study aims to understand how open innovation (OI) environments can help organizations in implementing knowledge sharing (KS) practices defusing KS barriers. Design/methodology/approach: An in-depth case study analysis on the strategic technology and innovation management (STIM) consortium at the Institute of Manufacturing of the University of Cambridge was performed during the 2019 and 2020 STIM program editions. To analyze data, this paper used the interpretive structural model on a sample of 20 managers participating in the STIM consortium, and this paper carried out an exploratory in-depth case study analysis to validate the results. Findings: The findings shed light on the role of OI environments in defusing KS barriers in the process of inter-organizational KS. Originality/value: Notwithstanding the importance of KS practices among organizations, only a few studies have recognized and investigated the role played by OI arrangements in enhancing KS practices.